Challenges to providing work integrated learning to international business students at Australian universities. Issue 4 (9th November 2015) - Gribble, Catriona; Blackmore, Jill; Rahimi, Mark
Abstract : Purpose: – The purpose of this paper is to report on a three-year Australian study of international business and accounting students and the transition to employment. For international students seeking to differentiate themselves in a highly competitive global labour market, foreign work experience is now an integral part of the overseas study "package". Work-integrated learning (WIL) is seen to provide critical "employability" knowledge and skills, however, international students have low participation rates. The high value placed on WIL among international students poses challenges for Australia as well as opportunities. Understanding the issues surrounding international students and WIL is closely linked to Australia's continued success in the international education sector which has broad, long-term, social and economic implications. Design/methodology/approach: – This paper draws on 59 interviews with a range of stakeholders including international students, universities, government, employers and professional bodies. Central to the paper is an in-depth case study of WIL in the business and accounting discipline at one Australian university. Findings: – Providing international students with access to discipline-related work experience has emerged as a critical issue for Australian universities. The study finds that enhancing the employability skills of internationals students via integrated career education, a focus on English language proficiency and "soft skills" development are central to success in WIL. Meeting the growing demand for WIL among international students requires a multipronged approach which hinges on cooperation between international students, universities, employers and government. Originality/value: – This project aims to fill a critical knowledge gap by advancing theories in relation to international students and WIL. While there is a significant body of research in the fields of international education and WIL, there is an absence of research exploring the intersection between the two fields. The study will contribute to the advancement of knowledge in both fields by exploring the emerging issue of WIL and international students.